(untitled) (Anclajes, 2023)
The narrative about swimmers in Subacuática, by Melina Pogorelsky; El interior afuera, by María Lobo, and Sodio, by Jorge Consiglio, rethink the relationship between the experience of water and the practice of writing often analyzed in studies on regionalism and other literatures of the natural. The difference is that these aquatic spaces are swimming pools located in an urban environment. If writing occurs in relation to place, space and material; its form and process change along with the spatial conditions and characteristics. The question that guides the analysis of the three swimming novels is about the narrative that the motion in and with the water of the pool produces. On the one hand, what stories the swimmers tell about the material experience of the body in water. On the other, how the bodily intersection between “closed water” and swimmers affects the materiality of writing. In a preliminary way, it can be established that, just as the body in water is the place of a transformation or a passage, writing is modified in search of ways to account for the experience of the fluid.